2002
DOI: 10.1111/1467-8624.00460
|View full text |Cite
|
Sign up to set email alerts
|

Observational, Physiological, and Self–Report Measures of Children’s Anger: Relations to Reactive versus Proactive Aggression

Abstract: The goal of this study was to examine the relations of reactive versus proactive aggression to children's anger, as assessed using observational, physiological, and self-report measures. Anger was hypothesized to be related to reactive aggression, but not to proactive aggression. Children (N = 272 second-grade boys and girls) participated in a procedure in which they lost a board game and prize to a confederate who cheated. Skin conductance reactivity and heart rate reactivity were measured throughout the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
315
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(344 citation statements)
references
References 52 publications
(66 reference statements)
25
315
2
2
Order By: Relevance
“…Reliability, factor structure, and validity are adequate (e.g. Hendrickx et al 2003;Hubbard et al 2002). Reliabilities in the current study were excellent for both reactive and proactive aggression (α reactive =0.91, α proactive =0.86).…”
Section: Teacher Measuressupporting
confidence: 52%
See 1 more Smart Citation
“…Reliability, factor structure, and validity are adequate (e.g. Hendrickx et al 2003;Hubbard et al 2002). Reliabilities in the current study were excellent for both reactive and proactive aggression (α reactive =0.91, α proactive =0.86).…”
Section: Teacher Measuressupporting
confidence: 52%
“…Dodge and Coie (1987) used a similar peer nomination technique to measure getting angry easily and also failed to find a unique relation. Also, Hubbard et al (2002) found self-reported anger to be correlated with proactive aggression but not reactive aggression. These authors, however, did find a relation between angry nonverbal behaviors and reactive aggression.…”
Section: Discussionmentioning
confidence: 94%
“…Reactive aggression is believed to be driven by anger associated with a perceived threat, and has been shown to relate to anger and physiological arousal (Hubbard et al, 2002). The findings in this study support the relation of anger and physiological arousal to both reactive aggression and hostile attributions simultaneously.…”
Section: The Role Of Emotion In Hostile Attributionssupporting
confidence: 76%
“…The response differences could explain why the measure was not found to be related to aggression in this sample, though some literature using the same measure has also failed to find a significant relation with aggression (Hubbard et al, 2002). Future research should continue to use the measure with a variety of measures of aggression to determine if differences might exist in its' relation with parent-rated (as in the current study), teacher-rated, or observed aggressive…”
Section: Limitationsmentioning
confidence: 68%
“…It is associated with the frustration theory of aggression (Berkowitz 1989) and is accompanied by an activation of the autonomous system (Hubbard et al 2002). In contrast, proactive aggression is considered a non-provoked behavior that is motivated by the desire for personal gains or the domination of others (Vitaro and Brendgen 2005).…”
Section: Introductionmentioning
confidence: 99%